Duty and 'Euthanasia': the Nurses of Meseritz-Obrawalde - Benedict, Susan (Nursing ethics, 2007)
This article examines the actions and testimonies of 14 nurses who killed psychiatric patients at the state hospital of Meseritz-Obrawalde in the Nazi 'euthanasia' program. The nurses provided various reasons for their decisions to participate in the killings. An ethical analysis of the testimonies demonstrates that a belief in the relief of suffering, the notion that the patients would 'benefit' from death, their selection by physicians for the 'treatment' of 'euthanasia', and a perceived duty to obey unquestioningly the orders of physicians were the primary ethical reasons that were stated for their behavior. However, 20 years had elapsed between the killings and the trial, thus giving ample opportunity for the defendants to develop comfortable rationales for their actions and for their attorneys to have observed successful defenses of others accused of euthanasia.